Organic matter quality and dynamics in tropical soils amended with sugar industry residue - Jader Galba Busato (Revista Brasileira de Ciência do Solo, 2012)
Soil organic matter depletion caused by agricultural management systems have been identified as a critical problem in most tropical soils. The application of organic residues from agro-industrial activities can ameliorate this problem by increasing soil organic matter quality and quantity. Humic substances play an important role in soil conservation but the dynamics of their transformations is still poorly understood. This study evaluated the effect of compost application to two contrasting tropical soils (Inceptisol and Oxisol) for two years. Soil samples were incubated with compost consisting of sugarcane filter cake, a residue from the sugar industry, at 0, 40, 80, and 120 Mg ha-1. Filter cake compost changed the humic matter dynamics in both content and quality, affecting the soil mineralogical composition. It was observed that carbon mineralization was faster in the illite-containing Inceptisol, whereas humic acids were preserved for a longer period in the Oxisol. In both soils, compost application increased fulvic acid contents, favoring the formation of small hydrophilic molecules. A decrease in fluorescence intensity according to the incubation time was observed in the humic acids extracted from amended soils, revealing important chemical changes in this otherwise stable C pool.